Detection of Antibodies to Seven Priority Pathogens in Backyard Poultry in Trinidad, West Indies - Brown Jordan, Arianne (Vet Sci, 2018)
Backyard poultry farms in Trinidad and Tobago (T&T) play a vital role in providing food and income for rural communities. There is currently no information on the presence and circulation of pathogens in backyard poultry farms in T&T, and little is known in relation to the potential risks of spread of these pathogens to the commercial poultry sector. In order to address this, serum samples were collected from 41 chickens on five backyard farms taken from selected locations in Trinidad. Samples were tested for antibodies to seven priority pathogens of poultry by enzyme-linked immunosorbent assay (ELISA). Antibodies were detected in 65% (CI 95%: 50–78%) of the sampled birds for Infectious bronchitis virus (IBV), 67.5% (CI 95%: 52–80%) for Infectious bursal disease virus (IBDV), 10% (CI 95%: 4–23%) for Newcastle disease virus (NDV), 0% (CI 95%: 0–0%) for Avian influenza virus (AIV), 0% (CI 95%: 0–0%) for West Nile virus (WNV), 31.7% (CI 95%: 20–47%) for Mycoplasm gallisepticum/synoviae and 0% (CI 95%: 0–0%) for Salmonella enterica serotype Enteritidis. These results reveal the presence and circulation of important pathogens of poultry in selected backyard farms in Trinidad. The results provide important information which should be taken into consideration when assessing the risks of pathogen transmission between commercial and backyard poultry farms, as well as between poultry and wild birds.